PENGARUH PERMAINAN PUZZLE TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK PRASEKOLAH DI RA. ASSA’ADAH - Vina Angelin; Rindu Rindu; Astrid Novita (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Fine motor development in preschool children requires optimal stimulation through structured play activities. Limited variation in learning media may cause fine motor skills to develop less optimally. Puzzle play is one form of educational play tool that can train hand–eye coordination through arranging and matching picture pieces. This study aimed to determine the effect of puzzle play on fine motor development in preschool children at RA. Assa’adah in 2025. This research used a quantitative method with a pre-experimental one group pretest–posttest design. The sample consisted of 30 preschool children selected using a total sampling technique. The research instruments included the Pre-Screening Developmental Questionnaire (KPSP) for fine motor aspects and an observation checklist. Data were analyzed using the Wilcoxon Signed Ranks Test because the data were not normally distributed. The results showed an improvement in fine motor skills after the puzzle play intervention. Statistical analysis revealed a Z value of -4.443 with a p-value of 0.000 (p < 0.05), indicating a significant difference between fine motor development before and after the intervention. In conclusion, puzzle play has a significant and effective effect on improving fine motor development in preschool children at RA. Assa’adah.